Resensi Sumber Daya Perikanan Zona Ekoton Ekosistem Mangrove-Lamun Di Teluk Youtefa Kota Jayapura Provinsi Papua - John Dominggus Kalor; Kalvin Paiki (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Mangrove and seagrass ecosystems have important functions and roles in coastal and marine waters, as an ecological buffer system, habitat for various types of fish and aquatic biota, as well as a biosystem of energy flow for the aquatic environment in Youtefa Bay, Jayapura. This study was conducted to calculate and review the mangrove and seagrass ecosystem fisheries affected by ecosystem damage and pollution. Data collection using fishing methods, vertical plankton sampling, and measurement of water quality parameters. Analysis of the data used: (1) analysis of the level of diversity using the Shannon-Wiener index, (2) analysis of dominance, (3) analysis of species composition (4) analysis of fish abundance, and (5) descriptive analysis. This study succeeded in obtaining 99 fish samples from 11 families and 12 fish species. The level of diversity is moderate (2.21) and the abundance of species is 73 individuals/ha. There were 5 dominant fish species associated with the ecotone zone of mangrove and seagrass ecosystems, namely Valamungil buchanani, Chanos-chanos, Gerres oyena, Pempheris schwenkii, and Pentapodus aureofasciatus. More fish were found in the seagrass and coral reef ecotone zones, namely 180 fish individuals caught from 11 families and 17 species of fish, with a high level of diversity (2.77), an abundance of species as many as 150 individuals/ha, and no dominant species. The review study of fishery resources in the ecotone zone shows very rapid degradation and decline in diversity, composition, and abundance in the waters of the mangrove, seagrass, and reef ecosystems of Youtefa Bay, Jayapura.Key Words: Fisheries; Mangroves; Seagrass; Youtefa Bay; Jayapura